Infrared nanoscopy and tomography of intracellular structures - Katerina Kanevche (Nature Portfolio, 2021)
Kanevche and colleagues present a combined imaging method employing scattering-type scanning near-field optical microscopy and Fourier-transform infrared spectroscopy to visualize the internal structures of cells. Demonstrating their method on eukaryotic and prokaryotic cells, they reveal chemically distinct regions of the cells.